Evidence from NMR interaction studies challenges the hypothesis of direct lipid transfer from L‐FABP to malaria sporozoite protein UIS3. (3rd January 2013) - Favretto, Filippo; Assfalg, Michael; Molinari, Henriette; D'Onofrio, Mariapina
Abstract UIS3 is a malaria parasite protein essential for liver stage development of Plasmodium species, presumably localized to the membrane of the parasitophorous vacuole formed in infected cells. It has been recently proposed that the soluble domain of UIS3 interacts with the host liver fatty acid binding protein (L‐FABP), providing the parasite with a pathway for importing exogenous lipids required for its rapid growth. This finding may suggest novel strategies for arresting parasite development. In this study, we have investigated the interaction between human L‐FABP and the soluble domain of Plasmodium falciparum UIS3 by NMR spectroscopy. The amino acid residue‐specific analysis of 1H, 15N‐2D NMR spectra excluded the occurrence of a direct interaction between L‐FABP (in its unbound and oleate‐loaded forms) and Pf‐UIS3. Furthermore, the spectrum of Pf‐UIS3 was unchanged when oleate or phospholipids were added. The present investigation entails a reformulation of the current model of host‐pathogen lipid transfer, possibly redirecting research for early intervention against malaria.